2006
DOI: 10.1017/asc2006105
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation and criteria of porcine fat firmness

Abstract: Fat quality, in particular, firmness is a main contributor to meat appearance, shelf life, taste, and human health. The current study was conducted to examine the fluctuation and criteria of porcine fat firmness. Several physiochemical methods were performed on 237 porcine perirenal fat samples that were obtained randomly from a commercial market. The relationship between perirenal fat and the middle subcutaneous fat layer was investigated to predict carcass fat quality. Each physiochemical property of the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…As expected, pigs in the D30-0wk treatment had significantly smaller (P = 0.04; Table 4) belly firmness scores, whereas pigs fed the 15% DDGS diets, without or with a withdrawal period, or pigs in the D30-3wk or D30-9wk treatment had similar belly firmness scores compared with pigs fed the control diets. Our results are in agreement with those from previous studies (Averette Gatlin et al, 2002;Nishioka and Irie, 2006). A greater firmness score describes a firmer belly.…”
Section: Belly Qualitysupporting
confidence: 94%
See 1 more Smart Citation
“…As expected, pigs in the D30-0wk treatment had significantly smaller (P = 0.04; Table 4) belly firmness scores, whereas pigs fed the 15% DDGS diets, without or with a withdrawal period, or pigs in the D30-3wk or D30-9wk treatment had similar belly firmness scores compared with pigs fed the control diets. Our results are in agreement with those from previous studies (Averette Gatlin et al, 2002;Nishioka and Irie, 2006). A greater firmness score describes a firmer belly.…”
Section: Belly Qualitysupporting
confidence: 94%
“…With an increase in C18:2 content or the IV of pork fat, fat firmness is reduced (Averette Gatlin et al, 2002;Nishioka and Irie, 2006). In the current study, C18:2 content and the IV of belly fat increased, but C18:0 content was reduced when pigs were fed increased dietary DDGS.…”
Section: Belly Qualitymentioning
confidence: 99%
“…As expected, belly firmness was reduced linearly (P < 0.01; Table 5) with increasing DDGS because of the linear increase in the IV of belly fat. Our results are in agreement with results from the previous studies conducted by Whittington et al (1986) and Nishioka and Irie (2006), in which the concentration of UFA, especially C18:2, of pork fat had a linear negative correlation with fat tissue firmness, whereas C18:0 has a positive correlation with fat firmness. Whitney et al (2006) reported that a dietary inclusion rate of up to 20% DDGS did not affect belly firmness, but belly firmness was reduced when pigs were fed diets containing 30% DDGS.…”
Section: Fatty Acid Composition and IV In Belly Fat 10th-rib Backfatsupporting
confidence: 93%
“…Feeding linseed to pigs increases the content of n-3 polyunsaturated fatty acids (PUFA) in muscle and adipose tissue (α-linolenic, eicosapentaenoic and docosahexaenoic acids), thus improving the nutritional quality of pork (Corino et al 2014). However, the increased concentration of UFA worsens the technological quality of pork in the meat processing industry because of inferior muscle and adipose tissue cohesiveness on cutting, lower fat firmness, and higher susceptibility to rancidity development (Nishioka and Irie 2006). Undesirable effects of UFA limit the use of plant oils and oilseeds in pig diets.…”
mentioning
confidence: 99%